Testbed versus simulation approach on RF communication with AAβ asymmetric encryption scheme on internet of things devices - Syed Farid Syed Adnan; Mohd Anuar Mat Isa; Habibah Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The revolution of the Internet of Things (IoT) has given a better way of monitoring things including anything that could gather data and share the information over the internet. Most of the connected things are using Device to Device (D2D) connection to make it available on the internet such as client to a broker or client to a server. However, when IoT devices such as embedded devices and sensors that are connected to the internet, it becomes an open path for attackers to acquire the data and data vulnerably will become an issue. Thus, data integrity might become an issue, or the attackers could temper the data and could cause a disastrous domino effect to the interconnected IoT devices. Therefore, the data security collected from the sensors is substantial even though it could be a single character transmitted. However, IoT sensors are low powered devices in term of CPU, storage, memory and batteries. Securing the devices such as integrating the encryption algorithm computations might give overhead to the sensors and draining the batteries even faster than it is predicted. Alternatively, this paper attempts to explore the capabilities of the asymmetric scheme on resource constrained devices for its communications. Thus, this paper presents an RF communication analysis of a low consumption asymmetric encryption, the AAβ (AA-Beta) especially on encryption section that is likely to be feasible on IoT devices to preserve the data integrity. The design of RF transmission has been considered to suit the RF transceiver capability to prevent data losses and error from occurring. The result shows that 2.35 times of RF transmits runtime increased compared to RF simulation runtime. Meanwhile, at the receiver side, the runtime increases 60% compared to the simulation.